Superparamagnetic FeO4 microspheres with positive surface charge and adjustable size, preparation method and application thereof
By regulating the high-temperature reaction conditions, superparamagnetic ferrooxide microspheres with adjustable particle size and positively charged surface were prepared, which solved the problems of uncontrollable nanoparticles size and lack of positive charge in the prior art, and improved their performance and potential in multiple application fields.
Patent Information
- Application Number
- CN202410429302.4
- Authority / Receiving Office
- CN · China
- Patent Type
- Patents(China)
- Current Assignee / Owner
- Filing Date
- 2024-04-10
- Publication Date
- 2025-04-25
- Estimated Expiration
- 2044-04-10
AI Technical Summary
The iron tetraoxide nanoparticles prepared in the prior art have problems such as uncontrollable particle size, lack of positive charge on the surface and uneven particle size, which limits their application in the fields of drug targeted delivery, biological separation, biological detection and medical imaging.
By dissolving iron salt, ammonium acetate and electrostatic stabilizer in ethylene glycol, reacting at high temperature and controlling the heating time, adjusting the number of primary Fe3O4 grains, thereby adjusting the particle size of Fe3O4 microspheres self-assembled nanograin, the preparation of superparamagnetic iron tetroxide microspheres with positive charge on the surface is realized.
The controllability and uniformity of Fe3O4 nano microsphere particle size is achieved, and the surface is positively charged, enhancing its application potential in the fields of magnetic, optical, biomedical and microwave absorbing materials.
Smart Images

Figure CN118206158B_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of nanomaterials, and in particular to a super sequential magnetic ferroferric oxide microsphere with a positively charged surface and adjustable size, and a preparation method and application thereof. Background Art
[0002] Magnetic nanomaterials, as the name implies, are magnetic materials with nanometer-scale particle sizes, and are currently mainly iron oxides. They not only have the quantum effect, surface effect, small size effect, and macroscopic particle tunneling effect of nanomaterials, but also have magnetic guidance, superparamagnetism, high coercivity, high magnetic susceptibility, low Curie temperature, and biocompatibility, making them widely used in drug targeted delivery, bioseparation, biodetection, and medical imaging.
[0003] The most commonly used method for preparing magnetic nanomaterials is the hydrothermal method, which is to obtain metal oxides by hydrolysis under high pressure and high temperature. These metal oxides have extremely low solubility in water, thus forming very fine crystals through supersaturation.
[0004] Existing patent CN113636601A discloses superparamagnetic ferroferric oxide nanoparticles and preparation and modification methods thereof, using ethylene glycol, ferric chloride hexahydrate, sodium citrate, and anhydrous sodium acetate, four simple and easily available raw materials, and using a hydrothermal method to quickly generate ferroferric oxide nanoparticles with good performance, but there are problems such as uncontrollable particle size. In addition, the prior art of ferroferric oxide nanoparticles prepared by the hydrothermal method also has problems such as lack of positive charge on the surface and uneven particle size, which limits its application in the fields of drug targeted delivery, biological separation, biological detection, and medical imaging. Summary of the invention
[0005] The purpose of the present invention is to overcome the problems existing in the above-mentioned prior art and to provide a superparamagnetic ferroferric oxide microsphere with a positively charged surface and adjustable size, as well as a preparation method and application thereof.
[0006] The purpose of the present invention can be achieved by the following technical solutions:
[0007] One of the technical solutions of the present invention is to provide a method for preparing superparamagnetic ferroferric oxide microspheres with positive surface charge and adjustable size, comprising the following steps:
[0008] S1, dissolving iron salt, ammonium acetate and electrostatic stabilizer in ethylene glycol to obtain a mixed solution;
[0009] S2. The mixed solution obtained in step S1 is reacted at high temperature and crystallized to obtain superparamagnetic ferroferric oxide microspheres.
[0010] In some specific embodiments, in step S1, the iron salt is ferric chloride hexahydrate.
[0011] In some specific embodiments, in step S1, the electrostatic stabilizer is selected from any one or more of γ-polyglutamic acid, casein, and soy protein.
[0012] The isoelectric points of γ-polyglutamic acid, casein, and soy protein are all macromolecular compounds in the acidic range. Under the alkaline conditions provided by ammonium acetate formed by the microspheres, the secondary nano-Fe3O4 microspheres are adjusted by the electrostatic stabilizer so that the surface of the secondary nano-Fe3O4 microspheres is positively charged. The electrostatic stabilizer also has the function of a surfactant, which not only limits the random Brownian motion of the particles in the reaction system, but also weakens the agglomeration between the particles, so that ordered secondary Fe3O4 nanoparticles assembled from primary Fe3O4 nanoparticles can be obtained.
[0013] In some specific embodiments, in step S1, the molar ratio of the iron salt to the ammonium acetate is 1:6 to 1:12.5.
[0014] In some specific embodiments, in step S1, the mass ratio of iron salt to ethylene glycol is 1:30 to 1:40.
[0015] In some specific embodiments, in step S1, the mass ratio of the iron salt to the electrostatic stabilizer is 2:1 to 4:1.
[0016] In some specific embodiments, in step S2, the temperature of the high temperature reaction is 160° C., and the time of the high temperature reaction is 0 to 240 min.
[0017] As the temperature rises, a supersaturated solution is formed, and primary crystals are continuously precipitated. As the heating time increases, the precipitated primary crystals increase until the critical concentration of saturation is reached. Therefore, by controlling the heating time at 160°C to affect the number of primary Fe3O4 crystals, the size of the secondary Fe3O4 crystals formed by crystallization at 200°C can be adjusted. When the total amount of iron salt is fixed, a longer heating time means the formation of more primary Fe3O4 crystals, so the final secondary Fe3O4 particle size decreases with the increase of heating time.
[0018] In some specific embodiments, in step S2, the crystallization temperature is 200° C., and the crystallization time is 8 to 24 hours.
[0019] In some specific embodiments, in step S2, the superparamagnetic ferroferric oxide microspheres obtained after the crystallization are further subjected to a washing treatment, specifically: the black precipitate obtained after crystallization and cooling is washed with ethanol and deionized water in sequence.
[0020] In some specific embodiments, when the mass of the iron salt in step S1 is 1.08 g to 108 g, the particle size of the superparamagnetic ferrosoferric oxide microspheres generated in step S2 is in the range of 80 to 600 nm.
[0021] The second technical solution of the present invention is to provide a superparamagnetic ferroferric oxide microsphere with a positively charged surface and adjustable size, which is obtained based on the preparation method described in one of the above technical solutions.
[0022] The third technical solution of the present invention is to provide an application of the superparamagnetic ferroferric oxide microspheres as described in the second technical solution in the fields of magnetism, optics, biomedicine, and microwave absorbing materials.
[0023] For example, in the field of optics, the superparamagnetic ferroferric oxide microspheres prepared by the present invention have good monodispersity and can be assembled into photonic crystals. Photonic crystals are artificial microstructures formed by periodic arrangement of media with different refractive indices. They are used in lasers, reflectors, curved optical paths, optical microcavities, photonic crystal fibers, etc. Unlike ordinary PCs, magnetic photonic crystals (MPCs) have the characteristics of instant response to external magnetic field behavior and more uniform diffraction color. Moreover, for two-dimensional MPCs, both the absolute bandgap width and its aspect ratio, that is, the ratio of the bandgap width to the center position of the bandgap, are much larger than non-magnetic PCs of the same structure. Therefore, the use of magnetic particles as building blocks of photonic crystals has considerable potential application value.
[0024] In the field of biomedicine, magnetic induction hyperthermia based on magnetic nanoparticles is a new type of tumor treatment method developed in recent years. Under the action of an alternating magnetic field, the magnetic moment of magnetic nanoparticles changes with the change of the direction of the external magnetic field. Magnetic nanoparticles will generate a certain amount of heat in the process of restoring their magnetic moment to their initial state. Cancer cells are more sensitive to temperature than ordinary cells. Cancer cells will die at 43-45°C, but normal cells can survive at this temperature. The LRT theory of paramagnetic nanoparticles can calculate the thermal efficiency of magnetic nanoparticles. From the LRT theory, it can be obtained that the thermal efficiency depends on the size of the magnetic nanoparticles and the frequency of the alternating magnetic field. Therefore, the size of the magnetic nanoparticles can be adjusted to obtain the desired optimal thermal efficiency and thus regulate the entire treatment process.
[0025] In the field of microwave absorbing materials, magnetic nanoparticles have strong microwave absorption properties and can absorb microwave radiation of a certain frequency, making them excellent microwave absorbing materials. Fe3O4 with different particle sizes has absorption properties for electromagnetic waves in different frequency ranges. The absorption efficiency increases with the increase of frequency, and the smaller the nanoparticle size, the higher the absorption efficiency. At present, in many military fields, Fe3O4 is widely used as a stealth nano coating for aircraft, missiles, warships and other weapons and equipment.
[0026] Compared with the prior art, the present invention has the following beneficial effects:
[0027] (1) The present invention uses only simple and easily available raw materials such as iron salt, ammonium acetate, electrostatic stabilizer and ethylene glycol, and adjusts the heating time of the high-temperature reaction, such as the heating time at 160°C, to produce different numbers of primary Fe3O4 grains, thereby adjusting the self-assembly growth of nano-grains into Fe3O4 nano-microspheres of different particle sizes, thereby achieving the controllability and uniformity of the particle size of the Fe3O4 nano-microspheres.
[0028] (2) The present invention creatively uses biomacromolecules with an electric point of less than 7, such as γ-polyglutamic acid, as electrostatic stabilizers. Under the alkaline conditions of microsphere formation, the surfaces of Fe3O4 nanospheres regulated by them can all carry positive charges. In addition, these electrostatic stabilizers also act as surfactants to obtain ordered secondary Fe3O4 nanoparticles assembled from primary Fe3O4 nanoparticles.
[0029] (3) The preparation method of Fe3O4 nanoparticles provided by the present invention has simple steps and is easy to promote and apply. It has good application prospects in the fields of magnetism, optics, biomedicine, microwave absorbing materials, such as drug targeted delivery, bioseparation, biodetection and medical imaging. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 This is a SEM image of the Fe3O4 nanospheres prepared in Example 1 of the present invention.
[0031] Figure 2 This is a SEM image of the Fe3O4 nanospheres prepared in Example 2 of the present invention.
[0032] Figure 3 This is a SEM image of the Fe3O4 nanospheres prepared in Example 3 of the present invention.
[0033] Figure 4 This is a SEM image of the Fe3O4 nanospheres prepared in Example 4 of the present invention.
[0034] Figure 5 This is a SEM image of the Fe3O4 nanospheres prepared in Example 5 of the present invention.
[0035] Figure 6 This is the Zeta potential distribution diagram of the Fe3O4 nanospheres prepared in Example 2 of the present invention.
[0036] Figure 7 This is the hysteresis loop diagram of the Fe3O4 nanospheres prepared in Example 2 of the present invention.
[0037] Figure 8This is a SEM image of the Fe3O4 nanospheres prepared in Comparative Example 1 of the present invention.
[0038] Fig. 9 This is the hysteresis loop diagram of the Fe3O4 nanospheres prepared in Comparative Example 1 of the present invention. DETAILED DESCRIPTION
[0039] The present invention is described in detail below in conjunction with the accompanying drawings and specific embodiments. This embodiment is implemented based on the technical solution of the present invention, and provides a detailed implementation method and specific operation process, but the protection scope of the present invention is not limited to the following embodiments.
[0040] In the following examples and comparative examples, unless otherwise specified, raw materials or processing techniques are conventional commercially available raw materials or conventional processing techniques in the art.
[0041] Embodiment 1:
[0042] This embodiment 1 provides a superparamagnetic ferroferric oxide microsphere with a positive surface charge and adjustable size, and the preparation method thereof specifically comprises the following steps:
[0043] (1) 40 mL of ethylene glycol was added to a three-necked flask, and 1.08 g of ferric chloride hexahydrate, 3.85 g of ammonium acetate, and 0.25 g of γ-polyglutamic acid were added in sequence under magnetic stirring, and dissolved by stirring.
[0044] (2) After complete dissolution, heat in a 160°C oil bath for 0.5 h, transfer to a 50 mL water-heated kettle, and then place in a 200°C oven for crystallization for 24 h.
[0045] (3) After the crystallization is completed, the hydrothermal reactor is taken out and cooled naturally. After washing with ethanol and deionized water for 3 times, the superparamagnetic Fe3O4 microspheres with positive surface charge and adjustable size are obtained.
[0046] like Figure 1 As shown, the average size of the Fe3O4 microspheres prepared in Example 1 is about 580 nm.
[0047] Embodiment 2:
[0048] This embodiment 2 provides a superparamagnetic ferroferric oxide microsphere with a positive surface charge and adjustable size, and the preparation method thereof specifically comprises the following steps:
[0049] (1) 40 mL of ethylene glycol was added to a three-necked flask, and 1.08 g of ferric chloride hexahydrate, 3.85 g of ammonium acetate, and 0.25 g of γ-polyglutamic acid were added in sequence under magnetic stirring, and dissolved by stirring.
[0050] (2) After complete dissolution, heat in a 160°C oil bath for 1 h, transfer to a 50 mL water-heated kettle, and then place in a 200°C oven for crystallization for 24 h.
[0051] (3) After the crystallization is completed, the hydrothermal reactor is taken out and cooled naturally. After washing with ethanol and deionized water for 3 times, the superparamagnetic Fe3O4 microspheres with positive surface charge and adjustable size are obtained.
[0052] like Figure 2 As shown, the average size of the Fe3O4 microspheres prepared in Example 2 is about 180 nm.
[0053] like Figure 6 This is the Zeta potential distribution diagram of Fe3O4 nanospheres. It can be seen that the results of three parallel measurements are all around +7mv.
[0054] like Figure 7 This is the hysteresis loop diagram of Fe3O4 nanospheres. The magnetic saturation intensity of the magnetic beads is 73emu / g.
[0055] Embodiment 3:
[0056] This embodiment 3 provides a superparamagnetic ferroferric oxide microsphere with a positive surface charge and adjustable size, and the preparation method thereof specifically comprises the following steps:
[0057] (1) 40 mL of ethylene glycol was added to a three-necked flask, and 1.08 g of ferric chloride hexahydrate, 3.85 g of ammonium acetate, and 0.25 g of γ-polyglutamic acid were added in sequence under magnetic stirring, and dissolved by stirring.
[0058] (2) After complete dissolution, heat in a 160°C oil bath for 2 h, transfer to a 50 mL water-heated kettle, and then place in a 200°C oven for crystallization for 24 h.
[0059] (3) After the crystallization is completed, the hydrothermal reactor is taken out and cooled naturally. After washing with ethanol and deionized water for 3 times, the superparamagnetic Fe3O4 microspheres with positive surface charge and adjustable size are obtained.
[0060] like Figure 3 As shown, the average size of the Fe3O4 microspheres prepared in Example 3 is about 100 nm.
[0061] Embodiment 4:
[0062] This embodiment 4 provides a superparamagnetic ferroferric oxide microsphere with a positive surface charge and adjustable size, and the preparation method thereof specifically comprises the following steps:
[0063] (1) 40 mL of ethylene glycol was added to a three-necked flask, and 1.08 g of ferric chloride hexahydrate, 3.85 g of ammonium acetate, and 0.25 g of γ-polyglutamic acid were added in sequence under magnetic stirring, and dissolved by stirring.
[0064] (2) After complete dissolution, heat in an oil bath at 160°C for 3 h, transfer to a 50 mL water-heated kettle, and then place in an oven at 200°C for crystallization for 24 h.
[0065] (3) After the crystallization is completed, the hydrothermal reactor is taken out and cooled naturally. After washing with ethanol and deionized water for 3 times, the superparamagnetic Fe3O4 microspheres with positive surface charge and adjustable size are obtained.
[0066] like Figure 4 As shown, the average size of the Fe3O4 microspheres prepared in Example 4 is about 80 nm.
[0067] Embodiment 5:
[0068] This embodiment 5 provides a superparamagnetic ferroferric oxide microsphere with a positive surface charge and adjustable size, and the preparation method thereof specifically comprises the following steps:
[0069] (1) 40 mL of ethylene glycol was added to a three-necked flask, and 1.08 g of ferric chloride hexahydrate, 3.85 g of ammonium acetate, and 0.25 g of soy protein were added in sequence under magnetic stirring and dissolved by stirring.
[0070] (2) After complete dissolution, heat in a 160°C oil bath for 1 h, transfer to a 50 mL water-heated kettle, and then place in a 200°C oven for crystallization for 24 h.
[0071] (3) After the crystallization is completed, the hydrothermal reactor is taken out and cooled naturally. After washing with ethanol and deionized water for 3 times, the superparamagnetic Fe3O4 microspheres with positive surface charge and adjustable size are obtained.
[0072] like Figure 5 As shown, the average size of the Fe3O4 microspheres prepared in Example 5 is about 200 nm.
[0073] Comparative Example 1:
[0074] Compared with Example 2, most of the above are the same, except that γ-polyglutamic acid is not added. The preparation method specifically comprises the following steps:
[0075] (1) Add 40 mL of ethylene glycol into a three-necked flask, and add 1.08 g of ferric chloride hexahydrate and 3.85 g of ammonium acetate in sequence under magnetic stirring, and dissolve by stirring.
[0076] (2) After complete dissolution, heat in a 160°C oil bath for 1 h, transfer to a 50 mL water-heated kettle, and then place in a 200°C oven for crystallization for 24 h.
[0077] (3) After the crystallization is completed, the hydrothermal reactor is taken out and cooled naturally. The Fe3O4 microspheres are washed with ethanol and deionized water for three times each to obtain Fe3O4 microspheres.
[0078] like Figure 8 As shown, the Fe3O4 microspheres prepared in this comparative example have surface defects and agglomeration occurs. The surface charge is not enough to stabilize the microspheres, so γ-polyglutamic acid is indispensable.
[0079] like Fig. 9 : This is the hysteresis loop diagram of the Fe3O4 microspheres prepared in Comparative Example 1. The magnetic saturation intensity of the magnetic beads is 67emu / g, which is lower than the magnetic saturation intensity of the Fe3O4 microspheres prepared in Example.
[0080] In summary, it can be seen that by regulating the number of primary Fe3O4 grains produced, the particle size of nano-Fe3O4 microspheres grown by self-assembly of nano-grains can be adjusted.
[0081] The above description of the embodiments is to facilitate the understanding and use of the invention by those skilled in the art. It is obvious that those skilled in the art can easily make various modifications to these embodiments and apply the general principles described herein to other embodiments without creative work. Therefore, the present invention is not limited to the above embodiments, and improvements and modifications made by those skilled in the art based on the disclosure of the present invention without departing from the scope of the present invention should be within the scope of protection of the present invention.
Claims
1. A method for preparing superparamagnetic ferroferric oxide microspheres with positive surface charge and adjustable size, characterized in that: The steps include: S1, dissolving iron salt, ammonium acetate and electrostatic stabilizer in ethylene glycol to obtain a mixed solution; S2, reacting the mixed solution obtained in step S1 at high temperature and crystallizing it to obtain superparamagnetic ferroferric oxide microspheres; Wherein, in step S1, the electrostatic stabilizer is selected from any one or more of γ-polyglutamic acid, casein, and soy protein; the mass ratio of iron salt to electrostatic stabilizer is 2:1 to 4:1; In step S2, the temperature of the high temperature reaction is 160°C, and the time of the high temperature reaction is ≤240 min and not 0 min; the temperature of the crystallization is 200°C, and the time of the crystallization is 8 to 24 h; When the total amount of iron salt is fixed, the number of primary Fe3O4 grains formed during the high-temperature reaction is proportional to the time of the high-temperature reaction, and the particle size of the secondary Fe3O4 obtained after crystallization is inversely proportional to the time of the high-temperature reaction.
2. The method for preparing superparamagnetic ferroferric oxide microspheres with positive surface charge and adjustable size according to claim 1, characterized in that: In step S1, the iron salt is ferric chloride hexahydrate.
3. The method for preparing superparamagnetic ferroferric oxide microspheres with positive surface charge and adjustable size according to claim 1, characterized in that: In step S1, the molar ratio of the iron salt to the ammonium acetate is 1:6-1:12.
5.
4. The method for preparing superparamagnetic ferroferric oxide microspheres with positive surface charge and adjustable size according to claim 1, characterized in that: In step S1, the mass ratio of the iron salt to the ethylene glycol is 1:30-1:
40.
5. A superparamagnetic Fe3O4 microsphere with a positively charged surface and adjustable size, characterized in that: Obtained based on the preparation method described in any one of claims 1-4.
6. Application of the superparamagnetic ferroferric oxide microspheres with positive surface charge and adjustable size as claimed in claim 5 in the fields of magnetism, optics, biomedicine and microwave absorbing materials.
Citation Information
Patent Citations
Superparamagnetic response ferroferric oxide nano-particles and preparation and modification methods thereof
CN113636601A
Preparation method of mesopore-controllable magnetic microsphere
CN101863517A